COVID-19 Containment Measures and Expected Stock Volatility : High-Frequency Evidence from Selected Advanced Economies - Acharya, Viral; Liu, Yang.; Zhao, Yunhui (Washington, D.C. : International Monetary Fund, 2021)
We study the effect of COVID-19 containment measures on expected stock price volatility in some advanced economies, using event studies with hand-collected minute-level data and panel regressions with daily data. We find that six-month-ahead volatility indices dropped following announcements of initial or re-imposed lockdowns, and that they did not drop significantly following the easing of lockdowns. Such patterns are not as strong for three-month-ahead expected volatility and generally absent for one-month-ahead expected volatility. These results provide suggestive evidence for the existence of an intertemporal trade-off: although stringent containment measures cause short-term economic disruptions, they may reduce medium-term uncertainty (reflected in expected stock volatility) by boosting markets' confidence that the outbreak would be under control more quickly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Informal Economy; Underground Econom